Hubungan antara Pembicaraan Tubuh dengan Ketidakpuasan Bentuk Tubuh pada Remaja Pengguna Media Sosial - Kenny The; Anita Novianty (Jurnal Psikologi Teori dan Terapan, 2022)
The development of a positive or negative body image becomes very important, especially during adolescence. This study aims to determine the relationship between negative fat talk, negative muscle talk, and positive body talk with body dissatisfaction of adolescent social media users. Data was collected by online survey which included Body Shape Questionnaire-34 (BSQ-34) and Body Talk Scale (BTS). This research uses purposive sampling. Participants consisted of 221 women and 35 men who met the inclusion criteria. In accordance with the first hypothesis, the results of the analysis show that there is a significant positive relationship between negative fat talk in the below and above average groups with body dissatisfaction. In line with the second hypothesis, it was found there was a significant positive relationship between negative muscle talk with body dissatisfaction. However, the third hypothesis of this study was rejected because there was no significant relationship between positive body talk and body dissatisfaction. The results of this study have implications for those who want to promote a positive body image about the characteristics of the target that needs to be targeted and suggestions for intervention.